Assessing oral healthcare accessibility in elderly through geographic information systems: a scoping review - Lesa, Lenny; Md Sabri, Budi Aslinie; Md Bohari, Nor Faezah (Faculty of Dentistry, Universiti Teknologi MARA, 2025)
Disparities persist, especially for the elderly, in accessing oral healthcare. GIS was widely used in spatial aspects to examine access to oral healthcare services and highlight multiple factors that might influence access to healthcare facilities. This study aims to conduct a scoping review of the available literature on the accessibility of oral healthcare (OHC) for the elderly population across countries using GIS. Electronic search was performed in the following databases: PubMed, Scopus, Web of Sciences (WOS), and Science Direct. This review included all types of studies that use GIS or a comparative geospatial mapping program in studying the accessibility of oral healthcare for the elderly population, published in the English language, with no restrictions on location or publication date. Excluded were duplicates, non-peer-reviewed papers and studies without full text available. The population included the elderly aged 60 years and above. Nine studies were included in the final review. All studies are from high-income countries: Australia, the United States, Japan and Great Britain. The spatial analysis techniques utilised here include proximity, overlay, Kernel Density, statistical, and network analysis. Overall, elderly access to OHC appears sparse in rural regions; public transport, especially bus networks, improves access. Policymakers should enhance dental services in rural areas, integrate transportation with clinics, and improve infrastructure for the elderly by utilising GIS tools to identify underserved regions and increase access to oral healthcare.